Peran Strategi Kewirausahaan Menyongsong Tahun 2023 (Studium Generale Kewirausahaan) - Koerniawan Hidajat (Jurnal Pemberdayaan Nusantara, 2023)
One of the strategies for success in facing the era of globalization and industry 4.0 with business competition requires alternative various entrepreneurial strategies to engage in global competence. The year 2023 is the initial milestone for making changes after working from home due to the Covid-19 disaster in 2020. Alternative strategies for winning competence in business competition must be known by young entrepreneurs such as students. Through the generale stadium, the aim is to motivate students to be more active as intracurricular entrepreneurial activities, which both students are expected to add insight into entrepreneurship knowledge both scientifically and practically. individual for business.